Fish waste silage, a green process for low feedstock availability. A Review - Libonatti, Claudia Carina; Agüería, Daniela Alejandra; Breccia, Javier (Agronomía Mesoamericana, 2023)
Introduction. Different fishing activities generate a waste volume related to the processing species (viscera, heads and bones), the discards of the companion fauna, species of low commercial value and the losses related to handling problems. Fish meal production is the most common process for recovery nutrients from these fish processing byproducts. However, those places with reduced infrastructure or where the volume of wastes produced do not justified the economic equation for conversion into fish meal or oil, the biological silage could be the technology of choice to promote a sustainable waste management. Objective. To compilate, organize and summarize literature related to biological fermentation of fish waste and its applications. Development. A bibliographic review was carried out (January 1994 - December 2020) referring to the comprehensive use of fishing residues mainly focused on the use of lactic acid bacteria in fish waste fermentation. The information was organized in different sections: fish silage, lactic acid bacteria and carbohydrate sources for biological silage. Conclusions. The studies analyzed in this review highlight the possibility of using a wide variety of carbohydrate sources, biological starters and fish waste fermentation conditions. The satisfactory results show the potential use of fish waste in different applications. This work could contribute to the fisheries that decide to adopt this kind technology in order to provide an innovative and viable recycling bioeconomy.